​​Fleshy Entanglements in Development Aspirations​: Birth Position as a Site of Contestation in Bangladesh - Janet Elaine Perkins (Medicine Anthropology Theory, 2023)
Encouraging women to adopt a position of their choice during birth has long been among the calls of scholars and activists challenging medicalised models of childbirth rooted in patriarchy to allow women to own their birthing experiences rather than accept the passivity of a lithotomy position. The encouragement of women to adopt a position of their choosing is now integrated within global health policy. Based on fieldwork conducted in Dhaka and Kushtia district, Bangladesh, this article examines the promotion of non-supine birth positions promoted through international development entities in Bangladesh. It argues that despite its emancipatory appeal, when subsumed by international development logics, the birth position operates as a site of political contestation in which women are rendered peripheral within a broader constellation of development imaginaries and ends. Within this constellation, the birth position is circumscribed as a technical intervention amenable to metricisation. Rather than a ‘return’ to more ‘natural’ forms of birth, ‘non-supine’ birth positions when instrumentalised in this context, are broadly conceived of as ‘foreign’, and serve to expand the medicalisation of childbirth.